2017
DOI: 10.1002/cctc.201700516
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Designed Solid Acid Sites in the Low‐Temperature Production of ϵ‐Caprolactam

Abstract: Modern society is placing increasing demands on commodity chemicals, driven by the ever‐growing global population and the desire for improved standards of living. As the polymer industry grows, a sustainable route to ϵ‐caprolactam, the precursor to the recyclable nylon‐6 polymer, is becoming increasingly important. To this end, we have designed and characterized a recyclable SAPO catalyst using a range of characterization techniques, to achieve near quantitative yields of ϵ‐caprolactam from cyclohexanone oxime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The optimum p x value is listed in brackets. measurements, which show complete dissociation of methanol at room temperature 26 and infrared 47,48 and NMR measurements 48,49 which indicate the presence of hydrogen bonded methanol at room temperature. Work is in progress to resolve this problem.…”
Section: Implications For Mth Catalysismentioning
confidence: 89%
See 1 more Smart Citation
“…The optimum p x value is listed in brackets. measurements, which show complete dissociation of methanol at room temperature 26 and infrared 47,48 and NMR measurements 48,49 which indicate the presence of hydrogen bonded methanol at room temperature. Work is in progress to resolve this problem.…”
Section: Implications For Mth Catalysismentioning
confidence: 89%
“…Neutron spectroscopy techniques are becoming an increasingly significant tool in the study of zeolite catalysed processes, [23][24][25][26] and we have recently reported the characterisation by inelastic neutron scattering (INS) of a commercial ZSM-5 zeolite catalyst reacted with methanol in a 12 g scale fixed bed reactor for 3 days at 623 K and 673 K. 27 The catalyst remained active for aromatic production at both reaction temperatures, although the vibrational spectra of the used catalysts from both INS and diffuse reflectance infrared spectroscopy showed some differences between the coke species present at the two temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques based on neutron spectroscopy are of growing significance in the field of heterogeneous catalysis, 22 both in the study of the catalyst itself, 23,24 and investigation of the relevant molecular species upon adsorption. 25,26 Quasielastic neutron scattering (QENS) is particularly effective in the study of microporous catalysts, 27 allowing the measurement of molecular movements taking place over timescales of 2 ps-100 ns depending on the instrument, and thus it may be employed to measure both nanoscale diffusion, [28][29][30] and also local motions such as rotation.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, it is possible to keep increasing the amount of Si in the synthesis gel to enhance the concentration of active sites. However, in our previous work (Potter et al, 2017) we have shown that increasing the Si quantity leads to type III substitution and Si islanding, lowering the overall number of acid sites. We have therefore decided instead to keep the Si loading constant, relative to our SAPO-34 procedure, and instead add a second dopant.…”
Section: Introductionmentioning
confidence: 84%